A New Metaheuristic Optimization Algorithm, the Weighted Attraction Method - Friedl, G.; Kuczmann, M. (Acta Technica Jaurinensis, 2015)
The paper presents a novel, particle behavior--based metaheuristic global optimization method. The idea behind the algorithm is based on attraction between particles, and in some aspects it is similar to the particle swarm optimization, but the interaction between particles is realized in a completely different way. The paper shows the main steps of the technique and some possible modifications. After that the comparison of efficiency and the speed of convergence with different well-known algorithms on two objective functions will be shown.